2020
DOI: 10.1182/blood.2019000106
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial carrier homolog 2 is necessary for AML survival

Abstract: Abstract Through a clustered regularly insterspaced short palindromic repeats (CRISPR) screen to identify mitochondrial genes necessary for the growth of acute myeloid leukemia (AML) cells, we identified the mitochondrial outer membrane protein mitochondrial carrier homolog 2 (MTCH2). In AML, knockdown of MTCH2 decreased growth, reduced engraftment potential of stem cells, and induced differentiation. Inhibiting MTCH2 in AML cells increased nuclear pyruvate and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…6a-b). These results are supported by previous findings that MTCH2 suppresses mitochondrial fusion (18) and does not influence TCA cycle activity (23).…”
Section: Mtch2 Regulates Mitochondrial Metabolism and Cell Survival Signaling In Glioma Cellssupporting
confidence: 91%
“…6a-b). These results are supported by previous findings that MTCH2 suppresses mitochondrial fusion (18) and does not influence TCA cycle activity (23).…”
Section: Mtch2 Regulates Mitochondrial Metabolism and Cell Survival Signaling In Glioma Cellssupporting
confidence: 91%
“…MTCH2 is known to contribute to adipocyte function, regulation of lipid metabolism [40,42], and to be genetically associated with obesity [43]. However, MTCH2 clearly has a role outside of adipocytes, as inhibition of MTCH2 increases products of metabolism, such as pyruvate and pyruvate dehydrogenase [44] in both brain and muscle. Our gene set enrichment analysis further supports MTCH2 involvement across a wide array of metabolic processes (Fig.…”
Section: Mtch2 Chr11mentioning
confidence: 99%
“…MTCH2 is a member of mitochondrial carrier family and regulates cell apoptosis by modulating the activity of mitochondrial permeability transition pore (37). Previous studies examined the role of MTCH2 in several types of tumors, including mammary carcinomas (21,22) and acute myeloid leukemia (AML) (23). Intriguingly, the role of MTCH2 in these tumors were opposite in breast cancer and AML.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed the function of MTCH2 in acute myeloid leukemia (AML). Inhibiting MTCH2 decreased tumor growth and induced differentiation of AML cells (23). However, the role of MTCH2 in malignant glioma is not de ned.…”
Section: Introductionmentioning
confidence: 99%